Development of website-based learning media on the material of kingdoms in Indonesia and regional heroes phase B - Ilmiawan, Tri Agusta; Priyanto, Wawan; Fajriyah, Khusnul (Jurnal Bidang Pendidikan Dasar, 2024)
The development and advancement of technology has many positive and negative impacts and changes in various fields, especially in the field of education in Indonesia. This also raises new challenges from the many challenges that already exist. in the era of globalization now the spread of information is very fast, one of which is through internet websites, this must be utilized properly and maximally for the world of education, with many benefits expected to make it easier for students to receive information to add insight and enrichment of material, thus the media used for students to learn must also develop creatively and innovatively. The purpose of this research is to develop website-based learning media in phase B IPAS subjects.